Energy Absorption, CO2 Emissions and Economic Growth Sustainability in Nigeria - Omodero, Cordelia Onyinyechi; Uwalomwa, Uwuigbe (International Journal of Energy Economics and Policy, 2021)
Economic growth sustainability and environmental preservation have become a topical issue. This study emanates from the need to assess the starring role of energy ingestion in guaranteeing sustainable economic progression in Nigeria. The study investigates the influence of energy consumption and carbon dioxide emission on the economic growth of Nigeria from 2008 to 2019. In this study, we employ the multiple regression techniques to assess the impact of Electricity, CO2, primary energy and total labour force on GDP. Various indicative checks show that the model is appropriate and error-free. Out of the four energy sources examined, Electricity is found inconsequential in affecting the economic growth of Nigeria. The CO2 emission is positively significant, implying that the economy is growing with a high level of pollution in the environment. The primary energy consumption put forth a substantial harmful effect on economic progress, while the total labour force has a strong significant affirmative impression on fiscal progression. The study suggests the use of renewable energy to preserve the environment and sustain economic growth in the country. Keywords: Energy consumption, CO2, Electricity, primary energy, labour force, sustainable economic growth. JEL Classifications: J82, L71, L72, L94, Q01, Q43 DOI: https://doi.org/10.32479/ijeep.11055